Research Reviews, Israel, Antisemitism and Scales for Religious and Spiritual Assessment - Carey, Lindsay B. (Journal of religion and health, 2026)
This issue of JORH considers various systematic literature reviews and bibliometric analyses covering a diverse field of religion and health topics - reviews which can save a considerable amount of time for those involved in research, clinical or ethical decision-making. The second theme in this issue relates to healthcare research conducted in Israel, plus the broader international concern of antisemitism - which, despite the skeptics, continues to escalate around the world. The final theme covered in this issue considers the increasing development, validation and/or adaptation of scales for the measurement of religiosity, spirituality and healthcare practices.